Primitive neuroectodermal tumour of kidney: an unusual entity - Wadhwani, Deepa; Gangwal, Kumud; Bhargava, Shilpi; Shah, Ruchit; Tejwani, Shankar; Gauba, Rajat (Annals of Pathology and Laboratory Medicine, 2015)
Primitive neuroectodermal tumor (rPNET ) of kidney is an extremely rare tumour which occurs in children and youngÂ adults and has only a few published reports. The present case is of a 24-year-old female presenting with complaining ofÂ pain abdomen since 2-3 months duration. USG guided FNAC showed a cellular aspirate composed of small round toÂ oval cells with scanty or small amount of cytoplasm was seen. Cells were arranged in clusters with occasional microacinarÂ or papillaryÂ arrangement wasÂ also noted. TwoÂ possibilitiesÂ were suggested- 1.Carcinoid tumour, 2. small cellÂ anaplasticÂ carcinoma. HistopathologicalÂ andÂ immunohistochemicalÂ (IHC)Â correlation wasÂ done. AÂ highly malignant small cell neoplasm composed of small round cells having scanty cytoplasm and dense nuclei against hemorrhagic background was seen. IHC panel was performed and was found to be strongly positive for MIC-2 (CD99) and showed weak positivity for NSE and ki -67. A final diagnosis of Primitive Neuro-ectodermal Tumour of kidney was made.